Allocating a replenishment order among a family of items - Miltenburg, G. John; McMaster University, Faculty of Business (My University, 1983)
Inventory control models which provide co-ordinated control (or joint replenishment) of families of items are very useful in practice. An important component of these models is the algorithm for allocating a total replenishment order among the items in the family. In this paper the allocation algorithm from a new class of co-ordinated control models is discussed. Inventory position is modelled as a diffusion process, and both continuous review and periodic review situations are considered. This new class of co-ordinated control models has been shown to outperform existing models (IBM's IMPACT Inventory Control Package).
15, 6 p. : ; Includes bibliographical references (p. 14-15). ; "January 1983."
Keywords: Business; Business; Inventory control > Mathematical models